La acción de lesividad como mecanismo de control en Colombia (2015)
The possibility that humans make mistakes when making judicial decisions that affect not himself but others, mostly; justifies the administrative acts issued during the course of a process can be challenged by those who consider themselves affected by them, but despite all actions taken by the administration should be properly regulated and determined by law, we see that In light of the current standard, no specific reference is made to this action as a means of control that is obviously necessary to apply. Therefore, research in this paper aims at the doctrine and case law, that the action of the harmfulness as exhaustive control mechanism remains the norm, as an independent contentious action. The consequences of a constitutional nature, such as due process, legal uncertainty against acts emitted by public officials in Colombia, prompted us to investigate the existing regulation on issues such as the harmfulness; and it is still a major issue has not been treated with due thoroughness required. Therefore and on the basis of the comparison of the provisions of law, the review of jurisprudence and doctrine; we examine here the difficulty of implementing the same in terms of the gaps to which we refer as they can be resolved through legal interpretation